A comprehensive review on waste paper concrete - Solahuddin, Azuwa (Elsevier B.V., 2022)
Aggregate, sand, water and cement are the mixtures for concrete. Waste paper concrete (WPC) incorporates waste paper (WP) in a concrete mixture. Each year, WP production increases gradually. As a result, additional places are required for landfills, which consume energy, deplete natural resources and increase environmental pollution. The environmental pollution could be lessened by using WP in concrete. So, this comprehensive paper reviews the potential of WP by adding or substituting with fine aggregate, coarse aggregate and cement in concrete at 0%, 5%, 10%, 15% and 20%. This paper also reviews the WP's structures, physical and chemical properties. Moreover, the fresh, structural and durability properties of WPC, such as slump, modulus of elasticity, stress-strain and water absorption, are also reviewed in this paper. From this review, the concrete's fresh, structural, and durability properties increase with the incorporation of WP at 5% and 10% and decrease at more than 10%. There are some hydrated cement particles, as observed through the SEM. At 10% WP addition, the hydrated cement particles tend to increase the concrete strength more than the strength at 5% WP addition. It is apparent that the incorporation of WP brings significant desirable characteristics compared to ordinary concrete, which has no waste paper contents. WP can potentially have favourable properties to be used in concrete production by improving its properties and performance.